Cover Image, Volume 46, Issue 12. (9th August 2022) - Suh, Hyoung Suk; Sun, WaiChing
Abstract : The cover image is based on the Research Article Multi‐phase‐field microporomechanics model for simulating ice‐lens growth in frozen soil by Hyoung Suk Suh and WaiChing Sun https://doi.org/10.1002/nag.3408 .